Analisis Valuasi Ekonomi dalam Upaya Peningkatan Kualitas Ruang Terbuka Hijau di Kota Semarang (Studi Kasus: Taman Indonesia Kaya) - Fitra Fitra; Hadi Sasana (Universitas Diponegoro, 2021)
The study of the Taman Indonesia Kaya case study aims to: (1) identify people's perceptions of the existence of RTH Taman Indonesia Kaya, (2) estimate the economic value of the availability of RTH Taman Indonesia Kaya, (3) analyze the factors that affect the willingness to level of Willingness To Pay (WTP) visitors towards improving the quality of RTH Taman Indonesia Kaya. Primary data and secondary data are used to calculate the WTP value. Primary data were obtained from 62 respondents using Accidental Sampling and key persons. Secondary data were obtained from relevant agencies. Descriptive statistical analysis is used to answer the first aim of this research, in-depth interview is used to the second aim of this research and the Contingent Valuation Method with the Bidding Game technique is used to answer the third aim of this research. The results of the research using questionnaires showed the perception of visitors to Taman Indonesia Kaya, respondents rated quite good and had the potential to be developed with an average value of 6.5 out of 10 on all criteria. The results of the Contingent Valuation Method show that there are 90.32% who are willing to pay (Willingness to Pay), with an estimated total WTP value of Rp396,833,500 per year. All of the community’s willingness (WTP) factors have a significant effect, except for marital status. Based on these results, it can be used as a reference for the development strategy of Taman Indonesia Kaya and further development in efforts to increase Green Open Space in Semarang City.